Optimera sättet att föra in remsor i Ludvig Svensson’s virkmaskin - Eshagi, Leo; Höglind, William (My University, 2019)
Abstract The purpose of this report is to optimize Ludvig Svensson AB’s machine tools during conversion. The method used today is both time-consuming and not ergonomical for employees. The work was carried out at the company Ludvig Svensson in Kinna and Chalmers at Lindholmen and Johanneberg. The work involves systematical product development and construction to produce a better solution for strip threading in a machine changeover. A better solution would mean a faster and more ergonomic way of threading strips. At first the method used today was analyzed in the form of study visits, model building and time studies. With increased knowledge and product development, a number of concepts were made. With the help of the authors, the concepts were systematically evaluated at Ludvig Svensson together with staff in several rounds and more concepts were added along the way. With the systematical product development tool, concepts were eliminated until a final concept selection could be made. The chosen concept was analyzed and discussions at Ludvig Svensson led to several different variants of the chosen concept. In order to refine the concept, prototypes of different variants were designed to be set against each other and evaluated. After testing and evaluations on the different variants, a final model was created for the company to work on and apply in practice. To delimit the work, it doesn’t include how the concept is to be implemented at the company. This means that the work also does not deal with how the production of the chosen concept would be implemented.
Keywords: Produktion; Innovation och entreprenörskap (nyttiggörande); Maskinteknik; Production; Innovation & Entrepreneurship; Mechanical Engineering